Negara, Korporasi, dan Masyarakat Sipil: Dinamika Demokrasi dalam Konflik Agraria Kendeng, Jawa Tengah - Mega Arinda Pramessella; Tias Rahma Dewi; Revalyza Misbah; Nurdin Nurdin; Fullah Jumaynah (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
The agrarian conflict in the Kendeng Mountains, Central Java, arose due to the construction of a cement factory by PT Semen Indonesia, which was supported by the state through the issuance of environmental permits, even though several permits had been revoked by court decisions. The local community rejected the project because it threatened their water sources, environment, and livelihoods. This study aims to analyze the relationship between the state, corporations, and civil society in the agrarian conflict in Kendeng, as well as the role of civil society movements in responding to this conflict. The research uses qualitative methods with a literature study of journals and related news reports. Using Karl Marx's theory of conflict and Charles Tilly's theory of social movements, the study finds that the state tends to side with corporate interests, while civil society continues to build resistance through collective action, legal advocacy, public campaigns, and ecofeminist movements. The Kendeng conflict reflects the imbalance of power relations and the weakness of substantive democracy in natural resource management. The need for increased transparency in licensing, community participation, and ecological protection are the main solutions.